Pengaruh Iklim Organisasi dan Motivasi Kerja Karyawan terhadap Kinerja Karyawan pada PT Midi Utama Indonesia Tbk - Aryadillah Aryadillah (Universitas Bina Sarana Informatika, 2018)
The problem that is the study of this research is the gap between the existing and expected circumstances, then there is a problem. Existing conditions are; Organizational climate that is no longer conducive but still forced on each employee to be productive and have high work motivation, so if this is allowed to drag on, it is not impossible that every employee will have a poor performance in the company, causing workers to inconvenience and reduce employee performance. Research Objectives Analyze the Effect of Organizational Climate with Work Motivation, Analyze the Effect of Work Motivation with Employee Performance, Analyze Organizational Climate and Work Motivation on Employee Performance. The research method used is Explanatory Survey, and uses a five-scale questionnaire, Likert category, while the object of this research is employees of PT. Midi Utama Indonesia, Tbk Tangerang Branch Ciledug. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that the influence of Organizational Climate variables (X1) and Employee Motivation variables (X2) on Employee Performance (Y) is 41.7%. The influence of Organizational Climate variable (X1) on Employee Performance (Y) 37.4% and Employee Work Motivation (X2) on Employee Performance (Y) is 41.7%. The results showed that the Organizational Climate was in the